Stress and depression in the social and academic setting of dentistry students in 2020 - Espinoza Vilela, Francis Valeria (2021)
Aim: The new modality of virtual classes that dental students go through, it can have negative effects on psychological health and / or academic performance. The objective was to determine the relationship between stress and depression in the social academic environment in 2020 in dentistry students at the Southern Scientific University. Materials and Methods: The study was descriptive, observational, cross-sectional and prospective where 108 students of the Dentistry career from 6th to 10th cycle of the Southern Scientific University participated and these were evaluated by means of a questionnaire with the SISCO scale to measure stress academic and the BECK scale (BID II) was used for depression. Results: in the 6th cycle there is more probability of stress and depression; the age group most affected were students aged 19-22. The p value for the relationship between academic stress and depression was p <0.001 Conclusion: There are statistically significant differences between academic stress and depression in students from the 6th to the 10th cycle of the Stomatology career at the Southern Scientific University.